From Disparity to Sustainability: Social Identity, Perceived Fairness, and Climate Cooperation - EMILY J. HANSON; RICARDO REBOREDO (Czech Journal of International Relations)
In the International Relations (IR) literature, inequality has been identified as a major inf luence on climate policy cooperation and implementation. Identities formed by the multiple inequalities in the global order have become key organizing principles for climate negotiation and significantly affect whether policies are seen as fair. We focus on these inequality-related identities (IRIs) and present an analytical framework that translates concepts from Social Identity Theory for use in IR to systematically examine how IRIs affect perceptions of policy fairness and implementation. We contend that this framework is cross-scalar in character; that is, given the social basis of climate politics, the dynamics can be understood as social processes regardless of whether they are undertaken by states, international organizations, or individuals. We offer this framework as a tool for mobilizing insights from social psychology into IR research and understanding the ways social identities affect collective climate action.